2016
DOI: 10.3855/jidc.7573
|View full text |Cite
|
Sign up to set email alerts
|

Detection and identification of coxsackievirus B3 from sera of an Indonesian patient with undifferentiated febrile illness

Abstract: Introduction: Coxsackievirus B3 (CVB3) virus has been implicated as the causative agent of various outbreaks of clinical disease, including hand, foot, and mouth diseases, aseptic meningitis, acute myocarditis, and inflammatory cardiomyopathy. Methodology: Two hundred and nine undiagnosed cryopreserved specimens obtained from factory workers in Bandung, Indonesia, who displayed symptoms of acute febrile illness were gathered. Total RNA was isolated from serum and tested by conventional polymerase chain reactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

6
0

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 21 publications
0
23
0
Order By: Relevance
“…Southeast Asia is considered to be especially vulnerable to potential outbreaks of pathogenic viruses and a number of pathogenic viruses have been reported to circulate in this region. These include Nipah virus (NiV) (Looi and Chua, 2007), H5N1 (Adisasmito et al, 2013), Dengue virus (Sasmono et al, 2015;Dhenni et al, 2018), Rabies virus (Susilawathi et al, 2012), West Nile virus , Chikungunya virus (Kosasih et al, 2013;Riswari et al, 2016), Zika virus , Coxsackievirus virus (Wiyatno et al, 2016), Measles virus (Hartoyo et al, 2017), Rhinovirus C (Wiyatno et al, 2018), Japanese encephalitis virus (Gao et al, 2013), Seoul virus (Hofmann et al, 2018) etc. The 2019 novel coronavirus (2019-nCoV) which emerged in Wuhan, Hubei, China, has also been identified in this region (Huang et al, 2020).…”
Section: Molecular Biology Of Pathogenic Virusesmentioning
confidence: 99%
See 2 more Smart Citations
“…Southeast Asia is considered to be especially vulnerable to potential outbreaks of pathogenic viruses and a number of pathogenic viruses have been reported to circulate in this region. These include Nipah virus (NiV) (Looi and Chua, 2007), H5N1 (Adisasmito et al, 2013), Dengue virus (Sasmono et al, 2015;Dhenni et al, 2018), Rabies virus (Susilawathi et al, 2012), West Nile virus , Chikungunya virus (Kosasih et al, 2013;Riswari et al, 2016), Zika virus , Coxsackievirus virus (Wiyatno et al, 2016), Measles virus (Hartoyo et al, 2017), Rhinovirus C (Wiyatno et al, 2018), Japanese encephalitis virus (Gao et al, 2013), Seoul virus (Hofmann et al, 2018) etc. The 2019 novel coronavirus (2019-nCoV) which emerged in Wuhan, Hubei, China, has also been identified in this region (Huang et al, 2020).…”
Section: Molecular Biology Of Pathogenic Virusesmentioning
confidence: 99%
“…Firstly, the genetic material of the viruses is extracted, isolated and purified from the specimens. Types of specimens commonly collected are those which contain the maximum amount of the target virus (Johnson, 1990), for example, whole blood and oral swabs are collected and used for detection of Ebola virus (World Health Organization (WHO), 2014); posterior-pharyngeal (throat) swabs or nasal swabs for detection of avian influenza A(H5N1) virus (World Health Organization (WHO), 2006); respiratory, stool, and rectal swab (Chan et al, 2004a), sputum , urine, serum, plasma and peripheral blood leukocytes specimens (Mahony and Richardson, 2005) for detection of SARS-CoV; serum , plasma, urine (Corman et al, 2016), whole blood, amniotic fluid, cerebrospinal fluid (CSF), organ tissues such as placenta, fetal brain, eyes (Landry and George, 2017) for detection of Zika virus; saliva, CSF, tears, skin biopsy, urine for detection of rabies virus (Fooks et al, 2009), serum for detection of Coxsackievirus (Wiyatno et al, 2016), West Nile virus , Dengue virus (Fahri et al, 2013), blood for detection of Chikungunya virus , etc.…”
Section: Polymerase Chain Reactionmentioning
confidence: 99%
See 1 more Smart Citation
“…This region is considered as one of the hot spots of emerging viral diseases (Gronvall et al, 2015). The circulation of pathogenic viruses such as Nipah (Lam, 2003;Looi and Chua, 2007), SARS (Goh et al, 2006), H5N1 (Adisasmito et al, 2013), West Nile (Myint et al, 2014), dengue (Sasmono et al, 2015), Chikungunya (Kosasih et al, 2013;Riswari et al, 2016), Zika and coxsackievirus (Wiyatno et al, 2016) has been reported in this region.…”
Section: Pathogenic Viruses Of Biosecurity Concernmentioning
confidence: 99%
“…It is worthy to note, that working on these viruses is challenging as the viruses used as biothreat agents are dangerous making the need for the research activity to be performed at high and maximum levels of biocontainment (biosafety level 3 and 4) (Tree et al, 2015;Artika and Ma'roef, 2017). The unpredictability of future emergence and re-emergence of pathogenic viruses which pose biothreats demands development of local capacity to rapidly detect and characterize circulating pathogenic viruses (Ma et al, 2011;Agustiningsih et al, 2016;Wiyatno et al, 2016). In addition, local availability of diagnostic, therapeutic and preventive measures to protect and treat first responders and civilians from the consequences of bioterrorism with pathogenic viruses is critical.…”
Section: Laboratory Biosecurity Risk Managementmentioning
confidence: 99%